Super-Eddington accretion and feedback from the first massive seed black holes. Issue 3 (18th April 2019) - Regan, John A; Downes, Turlough P; Volonteri, Marta; Beckmann, Ricarda; Lupi, Alessandro; Trebitsch, Maxime; Dubois, Yohan
Abstract: Super-Eddington accretion on to massive black hole seeds may be commonplace in the early Universe, where the conditions exist for rapid accretion. Direct-collapse black holes are often invoked as a possible solution to the observation of supermassive black holes (SMBHs) in the pre-reionization Universe. We investigate here how feedback, mainly in the form of bipolar jets, from super-Eddington accreting seed black holes will affect their subsequent growth. We find that, nearly independently of the mass loading of the bipolar jets, the violent outflows generated by the jets evacuate a region of approximately 0.1 pc surrounding the black hole seed. However, the jet outflows are unable to break free of the halo and their impact is limited to the immediate vicinity of the black hole. The outflows suppress any accretion for approximately a dynamical time. The gas then cools, recombines, and falls back to the centre, where high accretion rates are again observed. The overall effect is to create an effective accretion rate with values of between 0.1 and 0.5 times the Eddington rate. If this episodic accretion rate is maintained for order 500 million years, then the black hole will increase in mass by a factor of between 3 and 300 but far short of the factor of 10 4 required for the seeds to become the SMBHs observed at z > 6. Therefore, direct-collapse black holes born into atomic cooling haloes and which experience strong negative mechanical feedback will require external influences (e.g. rapid major mergers with other haloes) to promote efficient accretion and reach SMBH masses within a few hundred million years.